Identifying the Relation between Fasting Blood Glucose and Glycosylated Haemoglobin Levels in Greek Diabetic Patients - Marilena Stamouli; Abraham Pouliakis; Antonia Mourtzikou; Anastasios Skliris; Ioanna Panagiotou; Evaggelia Marasidi; Emmanouil Mournianakis (Annals of Cytology and Pathology - Peertechz Publications, 2016)
Introduction: Diabetes Mellitus (DM) is associated with long-term damage, dysfunction, and failure of various body organs.Glycosylated haemoglobin (GHbA1c) is a significant biochemical marker in patients with DM which provides an estimation of long-term average glycaemia. The aim of this study was to evaluate the relation between fasting serum glucose (GLU) level and GHbA1c in DM patients and healthy controls, to evaluate the differences between male and female patients and to evaluate the correlation between estimated Average Glucose (eAG) and GLU. Materials and Methods: The study included 800 DM patients (448 male, 352 female), and 200 (100 male, 100 female) healthy control patients. We used statistical modeling and analysis to evaluate the data. Results: Via linear regression we found statistically significant linear relations between GLUand GHbA1c for female and male patients, male patients had higher mean level of GLU than female (+10.7mg/dL p<0.05), similarly for GHbA1c (+0.24% p<0.05). For healthy controls, neither linear relation nor gender difference was identified. Subsequently we calculated eAG on the basis of GLU level, we found a significant correlation Corr.Coeff.=0.56) between GLU and eAG for DM patients and no correlation (Corr.Coeff.=0.026) for healthy controls. These finding were consistent when the analysis was repeated separately for both genders, however with no difference between men and women. Conclusions: eAG and GLU values cannot be used in general population interchangeably. One strategy option could be the use of eAG levels together with GHbA1c values.